A case study of community-oriented policing system in two crime-prone barangays in Iloilo City under the jurisdiction of Police Precints I & 3 - Bernaldez, Cristina Arojo (2005.)
This study primarily deals with police-community relationship on the two crime-prone barangays in Iloilo City. It looked into the dynamics of police-community cooperation and collaboration as they geared towards in pursuing a safe place. It also examined their perception towards each other and public trust on police to establish partnership. In the process of achieving a safe community, they were challenged by the issues and problems towards crime prevention., In order to answer the objectives, the researcher used survey and key informant interviews to serve as primary data. Library research at UPV and Camp Delgado was also done. The findings of the study revealed that barangay residents were willing to cooperate on crime prevention efforts by menas of attending civic undertakings and reporting crimes. The police and other support groups also took participation by patrolling and giving feedbacks, as well as participation on lectures and trainings for public education and information. However, it showed that the police needed to initiate more lectures and trainings as well as dialogues. Communities have positive perception on police performance, they also trusted the police regardless of the issues raised by some of them. On the contrary, the police saw the residents as hostile. However, as they employed community interactions and strategies they have seen transformations on the behavior and lifestyles of the residents. Most of the issues and problems raised by the residents were more on police duty, visibility, and communication. The key informants raised the issues and problems on crime activities such as drug addiction and thefts, use of sports and leisure equipment and peace and security. The efforts on the employment of COPS on the two barangays seemed to be successful as manifested by the decline of crime rate.
Research Project (Undergraduate, Bachelor of Arts in Political Science-Community Development) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Peace and order -- Crime-prone barangays -- Case studies